IMPLEMENTASI TEKNIK PENYUTRADARAAN DALAM PROSES PEMBUATAN VIDEO COMPANY PROFILE SEKRETARIAT DAERAH KOTA BOGOR - Salsabila, Aliya; Alfi Rahmawati; Diadji Kuntoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This project is motivated by the need to optimize public communication media at the Regional Secretariat of Bogor City, particularly due to the absence of a company profile video that can deliver information clearly, attractively, and in an easily understandable. This study aims to examine the directing process as well as the application of the Technique 5C Cinematography technique and Auteur. The method used is a descriptive qualitative approach pre-production, production, and post-production. Implementation of the Technique 5C Cinematography is able to produce more structured visuals and support the flow of information delivery, while Auteur Theory provides consistency in visual style that strengthens the identity of the work. Video result is presents information audiovisually to the characteristics of digital media. Therefore, the application of well-planned directing techniques plays an important role in improving the quality and effectiveness of a company profile video as an institutional communication medium